Intersecting Shocks: The Combined Labor Market Impacts of Automation and Immigration - Patrick Bennett; Julian Vedeler Johnsen (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We study how the labor market shocks of automation and immigration interact to shape workers' outcomes. Using matched employer–employee data from Norwegian administrative registers, we combine an immigration shock triggered by the European Union's 2004 enlargement with an automation shock based on the adoption of industrial robots across Europe. Although these shocks largely occur in separate industries, we show that automation reduces earnings not only in manufacturing but also in construction, where tasks overlap with robot-exposed sectors. Importantly, workers jointly exposed to automation and immigration suffer earnings losses greater than those facing either shock in isolation. These losses are driven by downward occupational mobility into low-wage services and re-sorting into lower-premium firms. Even within the Norwegian welfare system, the ability of social insurance to offset these long-run earnings declines is limited. Our findings underscore the importance of analyzing labor market shocks jointly, rather than in isolation, to fully understand their distributional consequences.
Keywords: J01; J61; J24; 330; automation; immigration; labor market shocks